View-Adaptive Motion Estimation and Disparity Estimation for Low Complexity Multiview Video Coding - Shen, Liquan; Liu, Zhi; Yan, Tao; Zhang, Zhaoyang; An, Ping (IEEE transactions on circuits and systems for video technology, 2010)
The emerging international standard for multiview video coding (MVC) is an extension of H.264/advanced video coding. In the joint mode of MVC, both motion estimation (ME) and disparity estimation (DE) are included in the encoding process. This achieves the highest coding efficiency but requires a very high computational complexity. In this letter, we propose a fast ME and DE algorithm that adaptively utilizes the inter-view correlation. The coding mode complexity and the motion homogeneity of a macroblock (MB) are first analyzed according to the coding modes and motion vectors from the corresponding MBs in the neighbor views, which are located by means of global disparity vector. According to the coding mode complexity and the motion homogeneity, the proposed algorithm adjusts the search strategies for different types of MBs in order to perform a precise search according to video content. Experimental results demonstrate that the proposed algorithm can save 85% computational complexity on average, with negligible loss of coding efficiency.